Performance comparison of micro-neutralization assays based on surrogate SARS-CoV-2 and WT SARS-CoV-2 in assessing virus-neutralizing capacity of anti-SARS-CoV-2 antibodies. Issue 8 (26th August 2021) - Sekirov, Inna; Petric, Martin; Carruthers, Erin; Lawrence, David; Pidduck, Tamara; Kustra, Jesse; Laley, Jonathan; Lee, Min-Kuang; Chahil, Navdeep; Mak, Annie; Levett, Paul N.; Mendoza, Emelissa; et al.
Abstract : We compared neutralization assays using either the wild-type severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus or surrogate neutralization markers, using characterized sera. We found the results of the neutralization assays 75 % concordant overall and 80 % concordant for samples with high antibody levels. This demonstrates that commercial surrogate SARS-CoV-2 assays offer the potential to assess anti-SARS-CoV-2 antibodies' neutralizing capacity outside CL-3 laboratory containment.